The Role of Basic Infrastructure to Strengthen Economic Security in Eastern Indonesia - Firre An Suprapto; Agus Manshur; Sumedi Andono Mulyo; Editha Praditya; Fiktia Alfianita (The Journal of Indonesia Sustainable Development Planning, 2024)
This study aims to analyze the role of water infrastructure in supporting the development of leading commodities in Maluku and Papua, Indonesia. The 2020 Gross Regional Domestic Product (GRDP) dataset will be analyzed using the Location Quotient (LQ) technique to determine the leading sectors/base commodities with comparative advantages in the Maluku and Papua Provinces. Based on the Location Quotient (LQ) analysis results, it will be combined with a spatial approach to provide an overview of water resources and infrastructure. The results of this study show that water resource infrastructure is related to the housing settlement sector and agricultural commodities in Maluku and Papua. Increasing agricultural productivity has positive implications for Indonesia's food and economic security. Investment in water infrastructure development is needed to support leading sectors.